Manufacturing of flash lamp and studying its properties - Baghdad Science Journal (مجلة بغداد للعلوم)
This study presents the design of flash-lamps for pumped solid-state lasers. In this research have been study some of characters for flash lamp. The optimum pressure operation is found using different flash lamps about (600-4000) mbar. In conclusion, it was shown that the increase in pressure due to improve efficiency of radiation and decrease of temperature. Also this study illustrated the reason of decrease temperature is atomic number and due to increase of radiation efficiency.